2010
DOI: 10.1002/ps.2017
|View full text |Cite
|
Sign up to set email alerts
|

Digestive proteolytic and amylolytic activities of Helicoverpa armigera in response to feeding on different soybean cultivars

Abstract: The findings demonstrated that the cultivars L17 and Sahar were partially resistant to this pest, probably because of some secondary chemicals or proteinaceous protease inhibitors of these cultivars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
1
28
1
2
Order By: Relevance
“…Thus, gut protease inhibition and larval weight reduction can be attributed to the interference of inhibitors and phenolic Positive correlation (r = 0.6) between larval weight reduction and inhibition of gut proteases was observed (data not given), which justifies the possible role of inhibition of gut proteases resulting in limited availability of amino acids for larval growth. It could also be due to hyperproduction of gut proteases by larvae in response to protease inhibitors present in diet that exerted insect for energy and essential amino acids, leading to retarded growth (Naseri et al, 2010). Phytic acid incorporated in diet leads to larval weight reduction and mortality in Depressaria pastinacella and Trichoplusiani insects (Green et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, gut protease inhibition and larval weight reduction can be attributed to the interference of inhibitors and phenolic Positive correlation (r = 0.6) between larval weight reduction and inhibition of gut proteases was observed (data not given), which justifies the possible role of inhibition of gut proteases resulting in limited availability of amino acids for larval growth. It could also be due to hyperproduction of gut proteases by larvae in response to protease inhibitors present in diet that exerted insect for energy and essential amino acids, leading to retarded growth (Naseri et al, 2010). Phytic acid incorporated in diet leads to larval weight reduction and mortality in Depressaria pastinacella and Trichoplusiani insects (Green et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Larval midgut contains a complex enzymatic system including trypsin, chymotrypsin, elastases and carboxypeptidases which help in protein digestion. Protease inhibitors (PIs), which are predominant in legume seeds, disrupt the growth and development of insect by interrupting protein digestion (Naseri et al, 2010, Shaikh et al, 2014. Health and environment hazards of synthetic pesticides along with developed resistance of insect towards chemical pesticides have made researchers to explore other ways to confer insect resistance (Kranthi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction in larval weight and increase in mortality rate were observed when protease inhibitors from Capsicum annuum, chickpea and kidney bean were incorporated in artificial diet for bioassay during feeding trials of H. armigera (Tamhane et al, 2005;Kansal et al, 2008;Mittal et al, 2014). It has also been reported that crude/purified protease inhibitor from different sources inhibits digestive enzymes such as trypsin and chymotrypsin which results in larval and pupal growth reduction (Naseri et al, 2010, Pandey et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Različiti rezultati su pokazali da je aktivnost digestivnih enzima generalno viša na veštačkim dijetama u odnosu na različite biljke domaćine, zbog visoke nutritivne vrednosti i balansiranog sastava amino kiselina u veštačkim dijetama (Clissold et al, 2006;Hari et al, 2007;Kotkar et al, 2009;Naseri et al, 2010).…”
Section: Plastični Odgovori Digestivnih Enzima Na Nutritivni Stresunclassified